2019
DOI: 10.1186/s12889-019-7732-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of childhood tuberculosis and factors associated with unsuccessful treatment outcomes in Tigray, Ethiopia: a ten-year retrospective cross sectional study

Abstract: BackgroundChildhood TB is an indicator of a recent transmission of the disease in a community and it is estimated to constitute 15–20% of all TB cases in many of developing countries. However, only few studies which dominated by industrial countries were engaged to assess the situation. Therefore, this study was aimed to see epidemiology of childhood TB and factors associated with poor treatment outcome in developing country.MethodUsing retrospective cross-sectional study design; Socio-demographic and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
2
13
3
3
Order By: Relevance
“…In the multivariate analysis, HIV infection was the only variable independentlyassociated with the treatment outcome, with a risk of unfavorable outcome 2.5 times higher among children infected with HIV. Children with TB-HIV co-infection or unknown HIV status have a higher risk of death, adverse drug reactions, and treatment default (Kay et al, 2018;Jenkins et al, 2017;Mirutse et al, 2019). Similar results have been described in Brazil, where TB-HIV co-infected children are more likely to be institutionalized, readmitted after treatment default, and to have unfavorable outcomes (default and death) (Dos Santos Dias et al, 2015).…”
Section: Discussionmentioning
confidence: 62%
“…In the multivariate analysis, HIV infection was the only variable independentlyassociated with the treatment outcome, with a risk of unfavorable outcome 2.5 times higher among children infected with HIV. Children with TB-HIV co-infection or unknown HIV status have a higher risk of death, adverse drug reactions, and treatment default (Kay et al, 2018;Jenkins et al, 2017;Mirutse et al, 2019). Similar results have been described in Brazil, where TB-HIV co-infected children are more likely to be institutionalized, readmitted after treatment default, and to have unfavorable outcomes (default and death) (Dos Santos Dias et al, 2015).…”
Section: Discussionmentioning
confidence: 62%
“…The low treatment success rate of this study compared with WHO 2020 report may be attributed to the fact that nearly all of the studies included in this meta-analysis were among the three high TB-burden countries countries [7,9,10,13,14,[26][27][28][29][30]32,33,[36][37][38][39][40][41][42][43][44][45] and countries with high TB/HIV co-infection [25,31]. More than one-fives of the analyzed studies were also conducted before and during 2015 [9,[32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 79%
“…A total of 306,351 study participants with a sample size ranging from 227 in Ethiopia [41] to 170,017 in South Africa [37]; for studies conducted in Ethiopia and South Africa respectively. Most of the study populations were from regions that are currently listed under the WHO as high TB burden countries [7,9,10,13,14,[26][27][28][29][30]32,33,[36][37][38][39][40][41][42][43][44][45].…”
Section: Characteristics Of Study Setting and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A mathematical modeling study of burden of childhood TB in 22 high-burden countries showed that the predicted proportion of tuberculosis burden in children for each country is correlated with incidence, varying between 4% and 21%. 28 Although the national burden of childhood tuberculosis is not known in Ethiopia, retrospective studies conducted in Tigray region, Northern Ethiopia 31 and Southern Ethiopia 32 showed 8.1% and 13% among all notified tuberculosis cases, respectively.…”
Section: Discussionmentioning
confidence: 99%